Safety and efficacy of an 8-week regimen of grazoprevir plus ruzasvir plus uprifosbuvir compared with grazoprevir plus elbasvir plus uprifosbuvir in participants without cirrhosis infected with hepatitis C virus genotypes 1, 2, or 3 (C-CREST-1 and C-CREST-2, part A): two randomised, phase 2, open-label trials. (November 2017) - Gane, Edward J; Pianko, Stephen; Roberts, Stuart K; Thompson, Alexander J; Zeuzem, Stefan; Zuckerman, Eli; Ben-Ari, Ziv; Foster, Graham R; Agarwal, Kosh; Laursen, Alex L; Gerstoft, Jan; Gao, Wei; et al.
Summary: Background: New hepatitis C virus (HCV) therapies with pan-genotypic efficacy are needed. The goals of part A of C-CREST-1 and C-CREST-2 were to compare the efficacies of two doses (300 mg or 450 mg once daily) of uprifosbuvir (MK-3682; NS5B inhibitor) in an 8-week regimen combined with grazoprevir (NS3/4A inhibitor; 100 mg once daily) and an NS5A inhibitor, either elbasvir (50 mg once daily) or ruzasvir (MK-8408; 60 mg once daily), and to evaluate the safety and tolerability of these combination regimens in individuals infected with genotypes 1, 2, or 3. Methods: Part A of these phase 2, randomised, multicentre, open-label, clinical trials enrolled participants from 11 countries, aged 18 years or older, chronically infected with HCV genotypes 1, 2, or 3, with HCV RNA of at least 10 000 IU/mL, without evidence of cirrhosis, who had not received previous treatment for HCV infection. Within each HCV genotype, participants were randomly assigned (1:1:1:1) with a block size of 4, to open-label treatment to one of four treatment groups: grazoprevir (100 mg/day) plus ruzasvir (60 mg/day) plus uprifosbuvir (300 mg/day); grazoprevir (100 mg/day) plus ruzasvir (60 mg/day) plus uprifosbuvir (450 mg/day); grazoprevir (100 mg/day) plus elbasvir (50 mg/day) plus uprifosbuvir (300 mg/day); or grazoprevir (100 mg/day) plus elbasvir (50 mg/day) plus uprifosbuvir (450 mg/day), according to a computer-generated allocation schedule. Randomisation was centrally implemented using an interactive voice response system and integrated web response system. The primary endpoint was the proportion of participants achieving sustained virological response at 12 weeks (SVR12; HCV RNA less than the lower limit of quantitation at 12 weeks after the end of all study therapy) in the per-protocol analysis set, which included all participants who were randomised and received at least one dose of study drug. The trials are registered withClinicalTrials.gov, numbersNCT02332707 andNCT02332720 . Findings: 241 participants were randomised between Feb 18, 2015, and March 16, 2015. 240 participants completed 8 weeks of treatment and reached follow-up 12 weeks after the end of treatment. Of the four regimens, grazoprevir plus ruzasvir plus uprifosbuvir 450 mg had the most consistently high SVR12 (>90%) for participants infected with genotype 1 (21 [91%] of 23), genotype 2 (15 [94%] of 16), and genotype 3 (20 [91%] of 22). In particular, among those with genotype 2 infection, the grazoprevir plus ruzasvir plus uprifosbuvir 450 mg regimen had a higher SVR12 (15 [94%] of 16) than the grazoprevir plus ruzasvir plus uprifosbuvir 300 mg regimen (ten [71%] of 14), grazoprevir plus elbasvir plus uprifosbuvir 300 mg regimen (11 [69%] of 16), or grazoprevir plus elbasvir plus uprifosbuvir 450 mg regimen (nine [60%] of 15). Overall, the most common adverse events were headache (55 [23%] of 240), fatigue (47 [20%] of 240), and nausea (32 [13%] of 240). Two (<1%) of 240 participants had serious adverse events (pharyngeal abscess and keratitis), which were not considered drug related by the respective investigators. Interpretation: These results support further evaluation of the three-drug direct-acting antiviral agent regimen of grazoprevir 100 mg plus ruzasvir 60 mg plus uprifosbuvir 450 mg among a more diverse HCV-infected population, including those with compensated cirrhosis, previous treatment with an interferon-containing regimen, and HCV–HIV co-infection. Funding: Merck & Co, Inc.